Flipbooks' Support Of Problem-Based Learning and Its Impact On Critical Thinking Ability - Dewi Vebiyanti; Asih Miatun (Universitas Wiralodra, 2025)
Mathematics teaching needs to be carefully designed to promote complex cognitive skills, especially critical thinking skills, as an essential competence. However, the lecture and question-and-answer models that are still widely used are often unable to develop these skills optimally. This circumstance highlights the need for innovative learning models that actively engage students and utilize technology, in line with the Merdeka curriculum. The purpose of this study is to investigate the effectiveness of the flipbook-based model of PBL in improving students' mathematical critical thinking skills. Flipbooks in PBL provide a contextualized, visual, and student-centered approach that encourages collaboration, exploration, and reflection. The results of the Mann-Whitney hypothesis tests, as the data were not normally distributed and did not meet the requirements for a t-test, showed that students in the flipbook-based PBL group achieved a higher mean score than the lecture and question-answer model groups. The effect size (d) value of 1.01 is in the high category, indicating that this model has a positive impact on improving critical mathematical thinking skills and supports contextualized and collaborative learning.